Sistem Informasi Monitoring Perjanjian Kerja Sama Berbasis Web Pada PT Dayamitra Telekomunikasi Jakarta - Marsuyitno, Marsuyitno; Putri, Sukmawati Anggraeni; Utami, Lilyani Asri; Dwiantoro, Tino (STMIK Budi Darma, 2020)
The development of the telecommunications world is developing very rapidly throughout the world and is no exception in Indonesia. The telecommunications business mostly involves companies providing equipment and providing telecommunications infrastructure, in this case, towers. PT Dayamitra Telekomunikasi or also known as Mitratel is a subsidiary of PT Telkom Indonesia. Tbk, which is engaged in providing telecommunications infrastructure in Indonesia. In carrying out its business activities, PT Dayamitra Telekomunikasi has collaborated extensively with external parties in terms of land use for the construction of telecommunications towers. Land use is currently divided into two land categories, namely private land and government land. The current condition in managing cooperative assets is still done manually or not systematically so that it is not effective and a monitoring information system is needed to monitor the use of assets listed in this cooperation document. The monitoring information system that will be created is web-based which will facilitate the user in monitoring, updating the status of the monetize point quota listed in the employment agreement document with the government. The software used in making this monitoring information system uses the PHP and MySQL programming languages.